Effects of aging on the association between cerebrovascular responses to visual stimulation, hypercapnia and arterial stiffness - Flück, Daniela; Beaudin, Andrew E.; Steinback, Craig D.; Kumarpillai, Gopukumar; Shobha, Nandavar; McCreary, Cheryl R.; Peca, Stefano; Smith, Eric; Poulin, Marc J. (Frontiers in Physiology, 2014)
Aging is associated with decreased vascular compliance and diminished neurovascular- and hypercapnia-evoked cerebral blood flow (CBF) responses. However, the interplay between arterial stiffness and reduced CBF responses is poorly understood. It was hypothesized that increased cerebral arterial stiffness is associated with reduced evoked responses to both, a flashing checkerboard visual stimulation (i.e., neurovascular coupling), and hypercapnia. To test this hypothesis, twenty older (64±8y; mean±SD) and ten young (30±5y) subjects underwent a visual stimulation (VS) and a hypercapnic test. Blood velocity through the posterior (PCA) and middle cerebral (MCA) arteries was measured concurrently using transcranial Doppler ultrasound. Cerebral and systemic vascular stiffness were calculated from the cerebral blood velocity and systemic blood pressure waveforms, respectively. Cerebrovascular (MCA: young=76±15%, older=98±19%, p=0.004; PCA: young=80±16%, older=106±17%, p< 0.001) and systemic (young=59±9% and older=80±9%, p< 0.001) augmentation indices (AI) were higher in the older group. CBF responses to VS (PCA: p< 0.026) and hypercapnia (PCA: p≤0.018; MCA: p≤0.042) were lower in the older group. A curvilinear model fitted to cerebral AI and age showed AI increases until 60 years of age, after which the increase levels off (PCA: R2=0.45, p< 0.001; MCA: R2=0.31, p< 0.001). Finally, MCA, but not PCA, hypercapnic reactivity was inversely related to cerebral AI (MCA: R2=0.28, p=0.002; PCA: R2=0.10, p=0.104). A similar inverse relationship was not observed with the PCA blood flow response to VS (R2=0.06, p=0.174). In conclusion, older subjects had reduced neurovascular- and hypercapnia-mediated CBF responses. Furthermore, lower hypercapnia-mediated blood flow responses through the MCA were associated with increased vascular stiffness. These findings suggest the reduced hypercapnia-evoked CBF responses through the MCA, in older individuals may be secondary to vascular stiffening.